Stress appraisals influence athletic performance and psychophysiological response during 16.1 km cycling time trials. (July 2020) - Thompson, Mark A.; Toner, John; Perry, John L.; Burke, Rachel; Nicholls, Adam R.
Abstract: Objectives: We examined how stress appraisals were associated with emotions, coping behaviours, as well as subjective and objective measures of performance. Design: Prospective field- and laboratory-based studies. Methods: In Study 1, 192 athletes completed process-oriented psychometrics pertaining to the aforementioned constructs throughout a sporting competition. Study 2 utilised an experimental design to assess the causal influence of stress appraisals on performance, cortisol, and psychological variables. Thirty gender-matched athletes were randomly assigned to either a stress appraisal (e.g., challenge, threat, benefit, or harm/loss) or the control group. Participants completed three 16.1 km cycling time trials (TT) on a cycle ergometer, with their appropriate stress appraisal engendered via falsified performance feedback throughout the final TT. Salivary cortisol samples and psychometrics (e.g., appraisals, emotions, and coping) were collected before and after each TT. Results: The results of Study 1 revealed a sequential link between challenge stress appraisals and perceived goal attainment via pleasant emotions and task-oriented coping behaviours. Threat stress appraisals inversely related to goal attainment via unpleasant emotions and both distraction- and disengagement-oriented coping. In Study 2, no significant psychophysiological or performance differences were found across genders. The temporal orientation of stress appraisals influenced objective cycling TT performance. Benefit and harm/loss stress appraisals significantly facilitated or inhibited performance, respectively. Cortisol spikes were observed in the stress appraisal group's threat, challenge, and benefit, with a decline detected within the harm/loss group. Whilst the process of winning is physiologically stressful, the fear of defeat may be more stressful than losing itself. Conclusion: Stress appraisals influence subjective and objective performance, as well as neuroendocrine and psychological responses to stress. Highlights: A path analysis revealed an association between appraisal and performance. Temporal orientation of stress appraisals significantly effects cycling performance. The fear of losing induces a greater cortisol spike than the actual event of losing. Challenge and benefit appraisals may induce physiological "success stress". No significant psychophysiological or performance differences found between genders.